eParticipation in sports - Uran, C.; Wöllik, H.; Müller, A. (Procedia Engineering, 2016)
The term eParticipation in its traditional form is most frequently associated with eGovernment and eDemocracy. It describes approaches to maximize the amount of persons involved in the process of political or public decision-making. There have already been attempts to broaden the scope of eParticipation for the fields of tourism and cultural heritage. In this paper, we describe an approach to apply the methods of eParticipation to large scale sport events, which have a pre-defined start and finish. Currently, the tracking of athletes in such events has certain limitations. Either it has a coarse resolution, because it depends on the placement of RFID timing stations, or it is expensive to achieve for a large number of athletes if they are equipped with GPS trackers. In this paper we propose a new method to locate athletes in a fine resolution but without the drawbacks of installing additional infrastructure or equipping every athlete with a dedicated tracker. This is achieved by crowd-sourcing the acquisition of athlete tracking data. The knowledge of every spectator along the track who is willing to participate is being used to locate athletes at any given time. Thereby the spectators have the possibility to participate in a community which enables them to share the location of passing athletes using their smartphone and an app that communicates with a server. Simultaneously, they can track the athletes they care about on a live map via the smartphone app. In order to deliver reliable results, the system is able to differentiate between various data sources such as conventional timing stations, authenticated users and anonymous users. Different confidence levels are assigned to each of these data sources, which enables a reliable athlete tracking. The information that the users need can be found and delivered to them through the use of sophisticated data analysis. This in turn keeps the newly created ecosystem interesting for a broad variety of spectators. Furthermore, this paper presents the results generated by the proposed system at the Ironman World Championship 2015 in Hawaii.